2004
DOI: 10.1603/0022-0493-97.5.1699
|View full text |Cite
|
Sign up to set email alerts
|

Relative Fitness of Cry1A-Resistant and -Susceptible <I>Helicoverpa armigera</I> (Lepidoptera: Noctuidae) on Conventional and Transgenic Cotton

Abstract: Glasshouse and laboratory experiments were conducted to evaluate the relative fitness of Cry1A-susceptible and laboratory-selected resistant strains of Helicoverpa armigera (Hübner). Life history parameters of H. armigera larvae feeding on young cotton plants showed a significant developmental delay of up to 7 d for the resistant strain compared with the susceptible strain on non-Bacillus thuringiensis (Bt) cotton. This fitness cost was not evident on artificial diet. There was no developmental delay in the F1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
102
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(107 citation statements)
references
References 36 publications
4
102
1
Order By: Relevance
“…2b). Typically, Þtness costs affecting rs individuals are accompanied by lower Þtness for homozygous resistant (rr) individuals (Carriè re et al 2001(Carriè re et al , 2004Bird and Akhurst 2004; Huang et al 2005;Bird and Akhurst 2007), although some studies have reported Þtness costs only affecting rs individuals Wright 2001, Janmaat andMyers 2005). We do not know why a cost affecting only rs individuals was found for SAF97-H4.…”
Section: Discussionmentioning
confidence: 99%
“…2b). Typically, Þtness costs affecting rs individuals are accompanied by lower Þtness for homozygous resistant (rr) individuals (Carriè re et al 2001(Carriè re et al , 2004Bird and Akhurst 2004; Huang et al 2005;Bird and Akhurst 2007), although some studies have reported Þtness costs only affecting rs individuals Wright 2001, Janmaat andMyers 2005). We do not know why a cost affecting only rs individuals was found for SAF97-H4.…”
Section: Discussionmentioning
confidence: 99%
“…The slower larval development of resistant T. ni on BollGard II plants indicates that, in the field, there may be asynchrony of mating between the T. ni populations from non-Bt cotton and BollGard II cotton plants. Slower larval development on Bt plants than on non-Bt plants has been reported for several insect species, based on both laboratory and field observations (44)(45)(46)(47)(48). Asynchrony of mating between insects from non-Bt plants and Bt plants in the field has been reported to be a factor that may affect the refuge strategy for resistance management (44,49).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, if resistance entails a fitness cost, the spread of a recessive allele could be prevented by an appropriate resistance management strategy (Lenormand and Raymond, 1998;Carrière and Tabashnik, 2001;Carrière et al, 2004;Bates et al, 2005). Although fitness costs associated with Bt resistance were not always detected (eg Gould and Anderson, 1991;Tang et al 1997), they have been reported in many pests (Groeters et al, 1994;Trisyono and Whalon, 1997;Alyokhin and Ferro, 1999;Oppert et al, 2000;Carrière et al, 2001a, b;Akhurst et al, 2003;Janmaat and Myers, 2003;Higginson et al, 2005. Bird and Akhurst (2004 showed that, in H. armigera, most fitness costs associated with Bt resistance (eg a lower percentage of survival or a longer mean time to pupation) are recessive.…”
Section: Introductionmentioning
confidence: 99%